The Influence of Dimensions of Relationship Marketing Practices on Patient Satisfaction and Its Impact on Patient Loyalty at XYZ Pratama Clinic - Jessica Nethania Arunde; Margaretha Pink Berlianto (Dinasti International Journal of Education Management And Social Science, 2025)
This study was conducted to determine the factors that influence the level of outpatient satisfaction at the XYZ Primary Clinic and its impact on patient loyalty. This study involved 195 outpatients. Data collection was carried out by distributing questionnaires containing 5 questions with a Likert Scale of 1-5 based on the judgmental sampling method. Data were analyzed using the SEM PLS method. The results showed that conflict handling, competence and empathy had a significant positive effect on patient satisfaction. Trust, commitment, communication, and social bonds did not affect patient satisfaction. In addition, patient satisfaction had a positive and significant effect on patient loyalty at the XYZ Primary Clinic, where satisfied patients tended to return to use the service and recommend it to others. Patient satisfaction partially mediated each of the influences given by conflict handling, competence, empathy on empathy. The results of importance performance mapping show that empathy and conflict handling are things that are considered important by patients and have been implemented well. This means that empathy and conflict handling are factors that must be maintained. Social bonds and communication are considered important by patients but have not been implemented well. Further research can enlarge the population at other Primary Clinics, take diagnostic data.